Finiteness Properties of Minimax and $\mathfrak{a}$-Minimax Generalized Local Cohomology Modules - Kianezhad, A.; Taherizadeh, A. J. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
Let $R$ be a commutative Noetherian ring with nonzero identity, let $\mathfrak{a}$ be an ideal of $R$, and let $M$ and $N$ be two (finitely generated) $R$-modules. We prove that $H_{\mathfrak{a}}^i\left( {M,N} \right)$ is a minimax $\mathfrak{a}$-cofinite $R$-module for all $i